2013
DOI: 10.4103/2156-7514.109758
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging as an Adjunct to Ultrasound in Evaluating Cesarean Scar Ectopic Pregnancy

Abstract: Cesarean scar pregnancies (CSPs) are a relatively rare form of ectopic pregnancy in which the embryo is implanted within the fibrous scar of a previous cesarean section. A greater number of cases of CSPs are currently being reported as the rates of cesarean section are increasing globally and as detection of scar pregnancy has improved with use of transvaginal ultrasound (TVUS) with color Doppler imaging. Delayed diagnosis and management of this potentially life-threatening condition may result in complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 7 publications
(17 reference statements)
0
37
0
Order By: Relevance
“…1A) [18]. Intraoperative findings revealed that the bladder was densely adhered to the lower uterine segment and the gestational sac implanted through the cesarean scar.…”
Section: Patient Detailsmentioning
confidence: 99%
“…1A) [18]. Intraoperative findings revealed that the bladder was densely adhered to the lower uterine segment and the gestational sac implanted through the cesarean scar.…”
Section: Patient Detailsmentioning
confidence: 99%
“…MRI is very helpful in showing sac characterization, localization and whether there is an invasion of adjacent organs because it is a multiplanar imaging method and it has a high soft tissue resolution. Another advantage of the MRI is that it gives critical information for further treatment plan and guidance to surgeons [10].…”
Section: History Of Two Cesarean Sections and D And Cmentioning
confidence: 99%
“…MRI, compared to ultrasound, is more sensitive for the detection of placental invasion into the uterine wall. 9 Once uterine rupture has occurred it is best diagnosed based on clinical findings rather than with imaging due to the limited time available before irreversible physiologic damage occurs to the mother and fetus. Based on case reports, the most common conditions associated with uterine rupture include: prolonged deceleration in fetal heart rate or bradycardia, [10][11][12][15][16][17] abnormal pattern in fetal heart rate, [10][11][12][15][16][17] previously scarred uterus, [13][14][15] oxytocin stimulation of labor, 13,14 cephalopelvic disproportion, 13,14 grand multiparity, [13][14][15] abruptio placentae, 13 10,15 In most cases of acute uterine rupture there is little time to perform diagnostic imaging, and there is currently no strong evidence to support one imaging modality over another.…”
Section: Introductionmentioning
confidence: 99%
“…Given these limitations, ultrasound is considered to be the first line imaging tool to evaluate the status of a cesarean scar. 4,9 Magnetic Resonance Imaging (MRI) and Computed Topography (CT) are also useful imaging modalities. MRI is hypothesized to be superior to CT for evaluating the status of a cesarean scar because of its superior ability to evaluate soft tissue structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation